PENGARUH HUMAN CAPITAL DAN STRUCTURAL CAPITAL TERHADAP KINERJA KEUANGAN PERUSAHAAN SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2022-2024 - Barokah, Siti; Sri Ramlah; Wilson Candra Teguh Pratama; Syifa Nafiah; Sevia Krisdianti Nurhalizah (Universitas Sarjanawiyata Tamansiswa, 2025)
The purpose of this study is to analyze the effect of human capital and structural capital on the financial performance of companies in the Food and Beverage Sector listed on the Indonesia Stock Exchange during the observation period of 2022–2024. To achieve this objective, data collection was carried out through documentation obtained from the website www.idx.co.id. The data analysis techniques used include descriptive analysis, classical assumption testing, multiple regression analysis, and hypothesis testing. The results of the study found that human capital (VAHU) has a positive and significant effect on financial performance (ROA). Meanwhile, structural capital does not have a significant effect on financial performance (ROA) in Food and Beverage Sector companies listed on the Indonesia Stock Exchange for the 2022–2024 period.